Some factors influencing interobserver variation in classifying simple pneumoconiosis. Issue 5 (May 1985) - Musch, D C; Higgins, I T; Landis, J R
Abstract : Three experienced physician readers assessed the chest radiographs of 743 men from a coal mining community in West Virginia for the signs of simple pneumoconiosis, using the ILO U/C 1971 Classification of Radiographs of the Pneumoconioses. The number of films categorised by each reader as showing evidence of simple pneumoconiosis varied from 63 (8.5%) to 114 (15.3%) of the 743 films classified. The effect of film quality and obesity on interobserver agreement was assessed by use of kappa-type analytic procedures for measuring agreement on categorical data. Poor film quality and obesity both affected agreement adversely. Poor quality films were disproportionately frequent in obese individuals, as defined by the Quetelet index. On control of film quality by stratification, the effect of obesity on interobserver profusion agreement was no longer evident.